Migration governance and agrarian and rural development: comparative lessons from China, Ethiopia, Kyrgyzstan, Moldova, Morocco, Nepal and Thailand - Lamba, A.; Sugden, F.; Aderghal, M.; Fengbo, C.; Pagogna, R.; Masotti, M.; Dessalegn, Mengistu; Murzakulova, A.; Kharel, A.; Amzil, L.; Stirba, V.; Kuznetsova, I.; et al. (University of London, 2023)
The purpose of this policy brief is to draw together key comparative lessons on different types of migration governance interventions in the AGRUMIG project research regions and examine how they support positive feedback loops between migration and agrarian and rural development. This exploration offers stories of success and omission. Moving beyond the elusive triple-win situation on the benefits of migration for destination and origin countries, migrants themselves and the highly politicized domain of the migration-development nexus, our point of departure is that there are vital prospects for augmenting the positive impacts of migration for societies globally. This brief focuses on how migration governance interventions are potentially useful in maximizing the gains between migration and agrarian development in the sending communities in China, Ethiopia, Kyrgyzstan, Moldova, Morocco, Nepal and Thailand.